Fundamental but underrepresented: root carbon stocks in African montane forests - Yaffar, Daniela; Addo-Danso, Shalom D.; Powers, Jennifer S.; Meier, Ina C. (Frontiers in Forests and Global Change, 2023)
African montane forests harbor some of the greatest biodiversity worldwide, with high levels of species endemism. However, the loss of these forests through fragmentation, deforestation and climate change has been rapidly increasing in recent years. Montane forests in Africa are more susceptible to changes in climate than their lowland counterparts, yet their ecological value is still underrepresented. These montane forests have recently been highlighted as a major aboveground carbon (C) stock. The estimated 149.4 Mg C ha−1 from aboveground live trees surpasses estimates from the Intergovernmental Panel on Climate Change for these endangered forests, and exceeds reported values for neotropical montane and lowland forests by up to 70%. Despite the tremendous implications of these findings, coordinated and available research on the C storage potential of the other share of African montane forest biomass, that is in tree roots, is largely missing. Broadly estimated from the allometry of aboveground C stocks and from root:shoot ratios in lowland forests, more than 60 Mg C ha−1 can be stored in African montane forest roots, about 40% more than previously determined. While this broad estimation points at the potential importance of root C stocks in African montane forests, it also unveils a far-reaching knowledge gap. Here, we advocate for a more quantitative representation of the root C stock from dominant forest tree species of African tropical montane forests and ultimately for a better grasp on tree C stocks from this endangered ecosystem.